Educational videos: a didactic tool for strengthening English vocabulary through the development of affective learning in kids - Celis Nova, Jonnathan; Onatra Chavarro, Clara Isabel; Zubieta Córdoba, Any Tatiana (GIST – Education and Learning Research Journal, 2017)
The following paper seeks to develop a proposal, observing to what extent educational videos and affective learning can strengthen vocabulary in an EFL setting. This action research study was done with fifth grade students belonging to a public school, who showed a low degree of motivation in the English class, making it difficult to acquire the language. The instruments that were applied are pre/post-tests, pre/post questionnaires, field notes and class workshops. Grounded theory was implemented for the data analysis. Results evidence the enhancement students had in vocabulary acquisition along with educational videos and affective learning.